Trafficking of Mycobacterium tuberculosis Envelope Components and Release Within Extracellular Vesicles: Host-Pathogen Interactions Beyond the Wall - Layre, Emilie (Frontiers in Immunology, 2020)
Components of Mycobacterium tuberculosis (Mtb) envelope such as lipoproteins, lypoglycans, lipids, and glycolipids act as Pathogen Associated Molecular Patterns and/or antigens, hence contributing in different ways to the bacillus recognition, phagocytosis, and to immune responses modulation. However, Mtb envelope components are not only encountered at the bacillus-host direct contact but can act remotely from the bacillus envelope. Indeed, they are also released from the bacillus envelope and are detected in different compartments such as the infected cells endosomal compartments or in extracellular vesicles produced by the bacillus itself or by infected cells. Characterizing their trafficking is of main importance for our understanding of their role in host-pathogen interactions and consequently for their potential use as vaccine components. This review aims at providing an overview of the current knowledge of the nature of Mtb envelope components shuttled within extracellular vesicles, the interaction of these vesicles with host immune cells and the remaining black holes.